The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajplung.00417.2015
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of P2X7 attenuates hyperoxia-induced acute lung injury via inflammasome suppression

Abstract: -Increasing evidence shows that hyperoxia is a serious complication of oxygen therapy in acutely ill patients that causes excessive production of free radicals leading to hyperoxia-induced acute lung injury (HALI). Our previous studies have shown that P2X7 receptor activation is required for inflammasome activation during HALI. However, the role of P2X7 in HALI is unclear. The main aim of this study was to determine the effect of P2X7 receptor gene deletion on HALI. Wild-type (WT) and P2X7 knockout (P2X7 KO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…An increasing number of researchers believe that the NLRP3 inflammasome is essential for the development of ALI induced by LPS, mechanical ventilation, hyperoxia or burn (2629). Inhibition of NLRP3 with various methods could alleviate ALI (30, 31). However, the effect of EETs on activation of NLRP3 inflammasome is poor understood.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of researchers believe that the NLRP3 inflammasome is essential for the development of ALI induced by LPS, mechanical ventilation, hyperoxia or burn (2629). Inhibition of NLRP3 with various methods could alleviate ALI (30, 31). However, the effect of EETs on activation of NLRP3 inflammasome is poor understood.…”
Section: Discussionmentioning
confidence: 99%
“…OXIDATIVE STRESS IS A COMMON complication of numerous pathologies including cancer, diabetes, and Alzheimer's disease, and is occasionally the outcome of oxygen therapy when administered at concentrations of FI O 2 Ͼ 0.8 (13,21). Furthermore, it is well documented and widely known that oxidative stress is a precursor to elevated levels of reactive oxygen species (ROS) (19,29).…”
Section: -Hne; Ros; Oxidative Stress; Aldh2; Mitochondriamentioning
confidence: 99%
“…In addition, NLRP3 inflammasome can not only affect the body’s immune defense system, but also take part in the occurrence and development of various diseases, such as acute lung injury [4], diabetes mellitus [5], and atherosclerosis [6]. Recent researches have confirmed that inhibition of NLRP3 inflammasome could relieve bronchopulmonary dysplasia and hyperoxia-induced acute lung injury [7, 8], indicating that NLRP3 inflammasome may be a therapeutic target for hyperoxia-induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%